2015
DOI: 10.1242/jeb.128298
|View full text |Cite
|
Sign up to set email alerts
|

King penguins can detect two odours associated with conspecifics

Abstract: Recent studies on olfaction in penguins have focused on their use of odours while foraging. It has been proposed for some seabirds that an olfactory landscape shaped by odours coming from feeding areas exists. Islands and colonies, however, may also contribute to the olfactory landscape and may act as an orienting map. To test sensitivities to a colony scent we studied whether King penguins (Aptenodytes patagonicus) could detect the smell of sand, feathers or feces by holding presentations beneath their beaks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 16 publications
(20 reference statements)
2
10
0
Order By: Relevance
“…). Variations between individual VOC profiles found in our study might give rise to the observed differential responses of adult King Penguins to faeces and feathers of other adult King Penguins (Cunningham & Bonadonna ). However, chemical variation could also be influenced by other factors such as age (Martín & López ) and reproductive state (Caro et al .…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…). Variations between individual VOC profiles found in our study might give rise to the observed differential responses of adult King Penguins to faeces and feathers of other adult King Penguins (Cunningham & Bonadonna ). However, chemical variation could also be influenced by other factors such as age (Martín & López ) and reproductive state (Caro et al .…”
Section: Discussionmentioning
confidence: 55%
“…Olfaction might also be important in social communication as already reported in Humbolt Penguins Spheniscus humboldti, which show kin recognition based on olfactory cues (Coffin et al 2011). Odours from feathers and faeces may also relay information on individual identity, enabling recognition of their partner among a large number of individuals, and orientate animals back to the colony after foraging (Cunningham & Bonadonna 2015).…”
mentioning
confidence: 81%
See 3 more Smart Citations